FINITE ELEMENT MODEL FOR ANALYSIS OF CHARACTERISTICS OF SHROUDED ROTOR BLADE VIBRATIONS - Anatoliy Zinkovskii; Kyrylo Savchenko; Yevheniia Onyshchenko; Leonid Polishchuk; Abilkaiyr Nazerke; Bagashar Zhumazhanov (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2022)
The paper presents the approaches to FE modelling of blade airfoil, contact between the shrouds and operational damage. The regularities are established concerning the influence of the finite element type, finite element mesh and model of contact interaction on the spectrum of natural frequencies of blade assemblies. The use of the developed computational models is substantiated to determine the forced vibration characteristics of the selected objects of investigation. Based on the performed numerical experiments it was substantiated of finite element model selection for analysis of characteristics of shrouded rotor blade vibrations.